Pengaruh Motivasi dan Religiusitas terhadap Komitmen Guru Madrasah Ibtidaiyah di Kecamatan Pamulang Kota Tangerang Selatan - Aan Fadia Annur (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2020)
This research aimed to identify and analyze 1) The Influence of motivation on Islamic Primary School (MI) Teacher’s Commitment; 2) The effect of religiosity on Islamic Primary School (MI) Teacher’s Commitment 3) The Influence of motivation and religiosity on Islamic Primary School (MI) Teacher’s Commitment. The method used for this research was descriptive method with quantitative approach. The populations were all Islamic Primary School teachers in Pamulang, South Tangerang. The data were collected by using questioners of motivation, religiosity and teacher’s commitment. Those were analyzed by descripting and inferential whereas the hypothesis test used multiple linear regressions. Result: 1) There was influence between motivation on teacher’s commitment with the coefficient correlation 0,606, it was indicated that motivation gave the impact on teacher’s commitment 60,6 % in the strong category. 2) There was influence between religiosity on teacher’s commitment with the coefficient correlation 0,565, it was indicated that religiosity gave the impact on teacher’s commitment 56,5 % in the medium category. 3) There was simultaneously influence between motivation and religiosity on teacher’s commitment with the coefficient correlation 0,669.